Some thoughts on separation of powers: Westminster model versus American model - Ismail, Ibrahim (International Islamic University Malaysia, 2009)
The focus of this paper is of the working system of government based on the theory of separation of powers. The theory in its original idea is hardly implemented in the world today. Necessary modifications and adjustments ought to be made to suit the adopting countries. As a result of the theory, there exists two dominat world governmental systems, which have been championed by the United Kingdom and the United States of America. The UK's system is better known as the Westminster model or parliamentary system; whereas the USA's system is popularly known as the presidential system. Each system has its own strengths and weaknesses. This paper also highlights the influence of the theory through constitutional provisions and judicial pronouncements, which indicated the modification of the two models to suit countries like Malaysia.